Unilever Company / Nur Salehan Yaakub ...[et al.] - Yaakub, Nur Salehan; Mohd Susaimi, Nurul Diana; Mohd Salleh, Nurul Nadia (2008)
As a top maker of packaged consumer goods worldwide, Unilever operates in many countries, such as Asia, Africa, North America, the Middle East, Western Europe, and Latin America. The company's products cover several categories, including savory, dressings and spreads; ice cream and beverages; personal care; and home care. Unilever's brands include popular names Axe, Dove, Pond's, Suave, Vaseline, Signal, Snuggle, Surf, Slim Fast, Lipton, knorr Ben & Jerry's, Breyers, and Country Crock, among others. Unilever is part of the Unilever Group owned by the Netherlands-based Unilever N.V. and UK-based Unilever PLC. With 400 brands spanning 14 categories of home, personal care and foods products, no other company touches so many people's lives in so many different ways. Their brand portfolio has made them leaders in every field in which they work. From comforting soups to warm a winter's day, to sensuous soaps that make us feel fabulous, their products help people get more out of life. They constantly enhancing their brands to deliver more intense, rewarding product experiences. They invest €1 billion every year in cutting edge research and development, and have five laboratories around the world that explore new thinking and techniques to help develop their products